Eritema-papulosis form rosacea – results of immunohistochemical research of the condition of the lesions - Haritonova E.G. (Морфологія, 2011)
Studying and the analysis of links pathogenesis of eritema-papulosis forms of rosacea by means of a wide spec-trum of immunohistochemical markers became a research problem. Fo r the decision of tasks in view by the author it is used a material of 12 diagnosed cases eritema-papulosis forms of rosacea at men at the age from 32 till 64 years. Use of immunohis-tochemical methods of research has allowed to reveal new links in pathogenesis rosacea and to establish a role of some cellu-lar populations of a skin and cages of imm une system in disease progressing. Besides, at use of the offered scheme of treat-ment dynamics of immunohistochemical indicators was observed considerably more expressed at erit ema-papulosis forms. Treatment influence on an immune link was has been confirmed essential, concerning control, reduction of quantity CD4 + cages, and also changes in quantity CD1 а +, CD138 + that CD68 + cages. Essential re sult the offered scheme gives in a di-rection of suppression of fibrous changes in derma and myofib roblastic transformations dendroc ytes. Considerably the meta-bolism extracellular of matrix improves. Influence of treatment on a vascular component proves to be true reduction of densi-ty of vessels in parallel with decrease in expression VEGF.